Horatio Hornblower - Gruffudd, Ioan.; Lindsay, Robert, 1949-; Healy, Dorian; Byrne, Michael, 1943-; Bathurst, Robert, 1958-; Benson, Andrew; Grieve, Andrew; Forester, C. S. (Cecil Scott), 1899-1966.; United Productions, ltd.; Meridian Broadcasting; Arts and Entertainment Network ([New York] : A&E Home Video : Distributed by New Video Group, 2005)
The A&E miniseries based on Forester's novels of Horatio Hornblower, following his career from a reticent midshipman to a self-assured and courageous officer.
vol. I. Duel -- vol. II. Fire ships -- vol. III. Duchess and the devil -- vol. IV. Wrong war -- vol. V. Mutiny -- vol. VI. Retribution -- vol. VII. Loyalty -- vol. VIII. Duty.
Based on the Hornblower books by C.S. Forester.
Originally produced as a television mini-series in 1998.
Special features: exclusive new interview with Ioan Gruffudd; filmmaker commentary on films Loyalty and Duty; 3 bonus programs; about C.S. Forester; nautical terms and definitions; interactive 3D naval cannon; guide to royal warships; C.S. Forester biography; cast and crew biographies; photo gallery.
Ioan Gruffud, Robert Lindsay, Dorian Healy, Michael Byrne, Robert Bathurst.
DVD; Dolby 2.0 stereo.
Soundtrack in English.
Keywords: Hornblower, Horatio (Fictitious character) -- Drama; Sailors -- Drama; Films for the hearing impaired; Great Britain -- History, Naval -- 19th century -- Drama; Television mini-series.; Television adaptations; Sea stories